A review on lipid production from microalgae: Association between cultivation using waste streams and fatty acid profiles. (July 2019) - Ferreira, G.F.; Ríos Pinto, L.F.; Maciel Filho, R.; Fregolente, L.V.
Abstract: Microalgae are potential sources of high-value lipids, with essential fatty acids that provide health benefits, as the omega-3 polyunsaturated fatty acids. However, its cultivation and downstream processing is still not commercially viable for some applications due to high-water consumption and high costs mainly regarding energy demands and nutrients as nitrogen. Therefore, using waste streams in existing industries as carbon and nutrient sources, as well as evaluating the best methodologies for growth and lipid extraction are essential to viabilize this process. This review focused on the study of scenario the of using different microalgae species, integrating their cultivation into biorefineries using their wastewater and carbon dioxide combating water and air pollution, aiming lipid productivity and fatty acid profile with specific composition. It was found that culture medium conditions and cultivation systems are key elements in understanding the lipid production and can decisively affect the process performance. For example, closed photobioreactors with CO2 supply and light can provide higher photosynthetic efficiency and lipid accumulation, coupled with polyunsaturated fatty acid production. Wastewater use can reduce productivity and affect lipid composition, but CO2 injection can promote both higher biomass and lipid productivities; being Chlorella a potential candidate for implementation in industrial facilities once it showed high PUFA (around 1/3) and lipid content, up to 27%, grown in wastewater. Moreover, it is crucial to seek biomass fractioning to obtain different high-value products that will compensate for high capital and operating costs. Further evaluation of possible effects in the final product quality is required. Graphical abstract: Image 1 Highlights: Microalgae potential to integrate a biorefinery using waste to grow is discussed. Lipid productivity and fatty acid profile are related to cultivation conditions. Bioremediation can be achieved together with lipid accumulation in microalgae. Addition of CO2 during cultivation can improve both biomass and lipid productions. Wastewater's use can affect product quality and requires further investigation.